Validated Instruments of Quality of Life (QOL) in Patients With Acute Myeloid Leukemia (AML) and Other Cancers - Salas, Maribel; Henderson, Mackenzie; Wientzek-Fleischmann, Angelika; Islam, Zahidul; Tu, Nora; Bilitou, Aikaterini; Elsharkawy, Maggie; Stellmacher, Ulf (Frontiers in Pharmacology, 2020)
Purpose: Acute myeloid leukemia (AML) can negatively impact quality of life (QOL). Few QOL instruments are specific to and have been validated in AML. This review aims to identify QOL instruments that have been validated and summarize their psychometric properties reported in published literature. Methods: A literature review search was performed using PubMed and OVID (Biosis, Embase, MEDLINE) databases through January 1, 2019. Search terms included: QOL, health-related QOL, patient-reported outcomes and validity, reliability, validated, tools, instruments, test-retest, and leukemia myeloid acute, leukemia, myeloid, acute, acute myeloid leukemia. Articles were included if they focused on cancer and reported psychometric properties that could be extracted. Abstracts and their references were reviewed for inclusion. Results: Ten papers evaluating nine instruments were included. Functional Assessment of Cancer Therapy Leukemia (FACT-Leu) showed internal consistency of α=0.86-0.88, correlation with European Organisation for Research and Treatment of Cancer (EORTC) QLQ-Leu of ρ=0.29-0.63, and test-retest reliability of κ=0.861. FACT-F showed correlations with EORTC QLQ-C30 of r=0.40-0.83. Hematological Malignancy Patient-Reported Outcome (HM-PRO) showed intraclass correlation coefficient (ICC) of 0.94-0.98. EORTC-8D and EQ-5D-3L showed ICC=0.595, correlations with each other of ρ=0.137-0.634 and with EORTC QLQ-C30 of r=0.651-0.917. EORTC QLQ-C30 showed person separation reliability of 0.47-0.90 and patient-observer agreement of 0.85. Life Ingredient Profile (LIP) showed internal consistency of α=0.29-0.77 and test-retest reliability of κ=0.42-1.0. QOL-E showed correlation with FACT-general of R=0.71, internal validity of α=0.7, and test-retest reliability of standardized Cronbach’s α=0.7-0.92. EORTC QLQ-Leu showed internal consistency of α=0.6-0.79. Conclusion: Although several QOL instruments have been validated, more research is needed to determine the most clinically useful instruments in patients with AML.